Odpowiedzi

2010-03-22T17:18:56+01:00
A)23+9y=50
9y=50-23
9y=27/ :9
y=3
b)8y-36=24
8y=24+36
8y=60/ :8
y=7,5
c)-4c-46=-2
-4c=-2+46
-4c=44/ :(-4)
c=-11
d)13+2x=3
2x=3-13
2x=-10/ :2
x=-5
e)-7=5x+1
-5x=1+7
-5x=8/ :(-5)
x=-1,6
2010-03-22T17:18:56+01:00
A) 23 + 9y = 50 / - 23
9y = 27 / : 9
y = 3

b)8y-36=24 / -36
8y = -12 / : 8
y = -1.5

c) -4c - 46 = -2 /+ 46
-4c = 44 / : (-4)
c= -11

d) 13 + 2x =3 /-13
2x= -10 / :2
x=-5

e) -7=5x+1 /-1
-8=5x / : 5
x= -1.6
2010-03-22T17:19:14+01:00
A)23+9y=50
9y=50-23
9y=27 /9
y=3

b)8y-36=24
8y=24+36
8y=60 / 8
y=7,5

c)-4c-46=-2
-4c=-2+46
-4c=44 / -4
c=-11

d)13+2x=3
2x=3-13
2x=-10 / 2
x=5

e)-7=5x+1
-7-1=5x
-8=5x / 5
x=-1,6